Fast P3HT Exciton Dissociation and Absorption Enhancement of Organic Solar Cells by PEG‐Functionalized Graphene Quantum Dots. Issue 8 (5th January 2016) - Novak, Travis G.; Kim, Jungmo; Song, Sung Ho; Jun, Gwang Hoon; Kim, Hyojung; Jeong, Mun Seok; Jeon, Seokwoo
Abstract : PEG‐functionalized graphene quantum dots (GQDs) are shown to promote fast exciton dissociation in organic solar cells. Short‐chain PEG promotes the most favorable interaction with other organic layers, and the overall efficiency is improved by 36% when compared to the reference devices. The mechanism of enhancement is shown to be increased absorption due to fewer charges remaining in the bound state.